A fuzzy rule-based system to assess e-government technical interoperability maturity level. Issue 3 (19th August 2014) - Corrêa, Andreiwid Sh.; Mota, Alexandre de Assis; Mota, Lia Toledo Moreira; Corrêa, Pedro Luiz Pizzigatti
Abstract : Purpose: Our purpose is to present a system called NEBULOSUS, which is a fuzzy rule-based expert system for assessing the maturity level of an agency regarding technical interoperability. Design/methodology/approach: It introduces the use of Artificial Intelligence and fuzzy logic to deal with the imprecision and uncertainty present in the assessment process. To validate the system proposed and demonstrate its operation, we take into account the Brazilian technical interoperability maturity model, based on the Brazilian Government Interoperability Framework (GIF). Findings: With the system proposed and its methodology, it could be possible to increase the assessment process to management level and to provide decision-making support without worrying about technical details that make it complex and time-consuming. Moreover, NEBULOSUS is a stand-alone system, offers an easy-to-use, open and flexible structuring database that can be adapted by governments throughout the world. It will serve as a tool and contribute to governments expectations for continuous improvement of their technologies. Originality/value: This study contributes towards filling a gap in general interoperability architectures, which is a means to provide an objective method to evaluate GIF adherence by governments. The proposed system allows governments to configure their technical models and GIF in order to assess information and communication technology resources.